The cytotoxic activity of Sponges and Tunicates from Turkish Aegean Sea - Uras, I. S.; Mutlu, B.; Koc, R. C.; Konuklugil, B. (NATL INST SCIENCE COMMUNICATION-NISCAIR, 2022)
The enormous bioactive components of different species from marine habitats make them attractive candidates for the discovery of new therapeutic active substances in several diseases such as cancer. Sea sponge and tunicate materials are the ideal sources of new chemotherapeutics for various cancers due to their rich metabolites. The fundamental purpose of the current study is to investigate the cytotoxic activity of methanolic crude extracts of sponges (Agelas oroides and Cladocora caespitosa) and tunicates (Ascidiella aspersa and Styela clava) collected from the Aegean Sea. The cytotoxic activity and the anti-cancer activity of the extracts was carried out by sodium 3 & PRIME;- [1-(diphenyl aminocarbonyl)-3,4-tetrazolium]-bis (4-methoxy 6-nitro) benzene sulfonic acid hydrate (XTT) on gastric adenocarcinoma cell line AGS, prostate cancer cell line PC-3, neuroblastoma cell line SH-SY5Y, and mouse fibroblast cell line L929. The extracts of sponge and tunicate were found to cause different cytotoxic effects on different cancer cells, largely in a concentration-dependent manner. It is found that the extracts exhibited high anti-cancer activities in neuroblastoma and prostate cancer cell lines at concentrations of 3 and 5 mg/ml. No significant cytotoxic activity was found in L929 cells. In addition, the microscopic examination of cells treated with the extracts shows that the extracts cause morphological changes with cellular rounding, which could be associated with apoptosis.
Keywords: Anti-cancer activity; Cytotoxic activity; Marine natural products; Sea sponge; Tunicate; MARINE SPONGE; EXTRACTS; Oceanography